Calculation of the Frenet Serret apparatus of curves given by the intersection of two Implicit Surfaces in R3 usingWolfram Mathematica v.11.2 software - Burgos N., Graciela (2019)
Most elementary Differential Geometry texts address the study of Frenet-Serret apparatus of spatial curves from a parameterization thereof. However, it is possible to calculate the Frenet-Serret apparatus of given spatial curves as the intersection of two surfaces expressed in Cartesian form. In this work the new package, FSAparatus, coded in the language of the scientific software is presented Mathematica v. 11.2. The outputs obtained are entirely compatible with the own commands of Mathematica. This package could become a tool in the process of Teaching course learning differential geometry of undergraduate.